INVENTORY RISK BASED TECHNIQUE FOR SPARE PARTS UTILIZATION (Jurnal Teknologi (Sciences & Engineering), 2015)
The equipment breakdown due to unavailability of spare parts has incurred challenges for the manufacturing industry in managing the inventory. Consequently, the problem of spare parts unavailability has lead the organization towards unproductive and eventually impact the financial performance. Therefore, maintaining good system has direct connection with spare parts availability. The inventory planner always strive hard to ensure that the spare parts are always available for the maintenance used. Nevertheless, maintaining high inventories of spare parts often conflict from meeting the needs of equipment reliability for the manufacturing plant. In view of this situation, management of spare parts become critical in ensuring the equipment reliability. This paper describes an innovative risk quantification technique using Binary Decision Diagram (BDD) for the spare parts inventory control. The technique modified the BDD concept by translating the failure history into binary decision. From the binary process, the data will be converted into spare parts probability table and failure impact is analyzed. These two functions of risk, will be calculated in order gain the risk in monetary value.